Mandibular Bone Changes in Children and Adolescents with Type 1 Diabetes Mellitus in Different Metabolic Control States - Tercanlı Alkış, Hümeyra; Yağmur, Burcu; Parlak, Mesut; Karayılmaz, Hüseyin (Journal of Dentistry Indonesia, 2022)
Objective: The aim of this study is to evaluate the cortical and trabecular mandibular bone morphology of children and adolescents with type 1 diabetes mellitus (DM) and control group utilizing fractal dimension analysis (FDA) and different panoramic radiomorphometric indices through digital panoramic radiographic images (DPRIs). Methods: The study included 57 patients for the type 1 DM group (25 male and 32 female with a mean age of 11.5±2.4 years) and 57 patients for the control group (28 male and 29 female with a mean age of 10.5±2.1 years). The type 1 DM group was divided into the well-controlled, moderately-controlled, and poorly-controlled subgroups based on HbA1c. Mandibular cortical width (MCW) (according to Lengerton et al.) and panoramic mandibular index (PMI) (according to Benson et al.) were measured, mandibular cortical index (MCI) (according to Klemetti et al) and simple visual estimation (SVE) (according to Lee et al.) were evaluated, and FDA was conducted according to White and Rudolph, resulting in three areas of interest (IAs) being obtained in all of the DPRIs. Results: There was no significant difference between type 1 DM group and control according to the mean MCW, mean PMI measurements, MCI and SVE. The mean FD values were not significantly different between type 1 DM group and the control and between type 1 DM subgroups and control. Conclusion: This study revealed no cortical and trabecular bone changes in mandibula in children and adolescents with type 1 DM compared to the control group. In addition, metabolic control states of DM did not affect the bone structure.